The Prevalence of Occupational Injuries and Preventive Practices among Gem Mining Workers in Eheliyagoda Pradeshiya Sabha Division, Sri Lanka - Warnakulasuriya, S.S.P.; Abhayarathna, W.L.K. (Proceedings of 9th International Research Conference, KDU, Sri Lanka, 8th - 9th Sept 2016, 2016)
Attached

Mining remains one of the most perilous and hazardous occupations in the world. To achieve rapid economic development, people explore natural sources from the earth by mining. Sri Lanka is one of the leading country for gem industry. Though gem mining is associated with various occupational health problems, there is no evidence reported occupational injuries of gem miners in Sri Lanka. Determine the prevalance of occupational injuries and preventive practices used by the gem miners in Ehaliyagoda Pradesiyasaba division. This descriptive cross sectional study was carried out in a sample of (384) randomly selected gem miners. An interviewer administered questionnaire was used to collect data related to occupational injuries during the past 12 months and the preventive practices for occupational health problems. Descriptive statistics were applied to analyze data. The majority (88.8%) of the participants had experienced accidental cut injuries and 49.6 % of them had got injuries due to knocking with flying objects. One fourth (25%) of them had fallen from heights and experienced injuries to bone (17.2%) and head (27.9%) during the past. The workers' experience in accidental exposures to occupational Hazards include toxic earth gasses (21.1 % ), flooding and drowning (21.1%) and collapsing the walls of the tunnels (32.2%) during the past. None of the workers had used personal protective equipment. The majority (81.5 %) had used proper building ^ techniques inside the mines and kept first aid box in the mine (38.5 %). Cut injuries are common among gem miners followed by injuries due to flying objects. Gem | miners are at high risk of getting accidental exposer to the collapsing of walls, earth gases also flood and drowning. There should be standard health protective health “safety measures in gem mines
Keywords: Mining; Gem; Occupational injuries